Utilização do extrato etanólico de jabuticaba (Myrciaria cauliflora) no controle de Salmonella Heidelberg na produção de frangos de corte - Leonídio, Angélica Ribeiro Araújo (2018)
The objective of the present study was to evaluate the use of the ethanolic extract of of bark and seeds of Myrciaria cauliflora in the incubation of fertile eggs and in the feeding of broilers inoculated with Salmonella Heidelberg, observing possible beneficial and or protective effects of this phytogenic on health systemic effects of birds. Three experiments were carried out at the Experimental Center for Bird Diseases and Laboratory of Bacteriology of the Department of Veterinary Medicine of the Veterinary and Zootechnical School of the Federal University of Goiás. In the first experiment was evaluated the antimicrobial in vitro activity was evaluated and the minimum inhibitory concentration of ethanolic extract of M. cauliflora on Salmonella enterica different strains. In the second experiment, 320 fertile eggs distributed in randomized design were used in four treatments with 10 replicates each: CN - negative control group; EJ - group that received only the extract in the shell; SH - group that received only the bacterial inoculum in the shell; and SH + EJ - group that received the bacterial inoculum and the extract in the shell. The eggs incubated non-hatched were submitted to embryodiagnosis and processed for Salmonella in the embryos. The chicks born were housed until 10 days of age, during which time the collection and processing of samples for Salmonella research, serum biochemistry and hemogram were performed. In the third experiment, 336 one - day - old male chicks were distributed in randomized design in four treatments with seven replicates each: CN - negative control group; EJ - group that received only the vegetal extract in the diet; SH - group that received the inoculum bacterial in crop; and SH + EJ - group that received the bacterial inoculum in crop and the extract in the diet. Performance indexes, fecal excretion and presence of Salmonella in organs, organ biometry, intestinal histomorphometry, goblet cell counts and immune cells in organs and blood were evaluated. In the first experiment, the extract presented low inhibitory action on the strains of Salmonella enterica,, Salmonella Typhi, Salmonella Heidelberg and Salmonella Typhimurium. In the second experiment it was verified that the extract promoted less hatchability and higher embryonic mortality. The Salmonella isolation was higher in the embryo and meconium samples of the group that received the extract. At 10 days of age the extract reduced the excretion and colonization of the organs by Salmonella and the hematocrit and serum cholesterol level. In the third experiment it was verified that the extract increased the excretion of Salmonella in the inoculated birds and reduced the number of lymphocytes in the blood. It is concluded that the use of the ethanolic extract of bark and seeds of M. cauliflora presented weak antimicrobial activity in vitro for the strains of Salmonella enterica tested. In embryonated eggs its use is not feasible, however when added in the diet, it can stimulate the production of lymphocytes in lymphoid organs.